PENGARUH FINANCIAL LITERACY, FINANCIAL ATTITUDE, FINANCIAL SELF-EFFICACY, DAN SELF CONTROL TERHADAP FINANCIAL BEHAVIOR DALAM PENGGUNAAN PAYLATER (STUDI KASUS PADA MAHASISWA DI KOTA BANDUNG) - Febyanti Christanto; Devyanthi Syarif (Jurnal Akuntansi, Keuangan dan Teknologi Informasi Akuntansi, 2025)
This study aims to analyze the influence of financial literacy, financial attitudes, financial self-efficacy, and self-control on the financial behavior of students who use Paylater services in Bandung City. The research method used is a quantitative method with a non-probability sampling technique using the Snowball Sampling approach. The sample in this study consisted of 100 students taken from a student population in Bandung City of 305,421 people, based on data from the West Java BPS in 2025. The results of the study showed that partially, only the financial literacy variable had a significant effect on students' financial behavior. While the financial attitude, financial self-efficacy, and self-control variables did not have a significant effect. However, simultaneously, the four variables together had a significant effect on students' financial behavior, with a significance value of the F test of 0.009. The conclusion of this study is that financial literacy is a dominant factor that influences students' financial behavior in using Paylater services. Therefore, increasing financial understanding is very important in order to encourage wise and responsible financial behavior among students. Keywords : Financial Literacy, Financial Behavior, Paylater, Bandung City Students